Enhancing Students’ English Business Communication Skills Through the TSTS Learning Model at Balikpapan State Polytechnic - Damayanti, Lilik; Huda, Masrul; Rahmatika, Tia; Dwimas, Herdian (Universitas Pahlawan Tuanku Tambusai, 2026)
This research investigated the role of the Two Stay Two Stray (TSTS) cooperative learning method in developing students’ English for business communication skills by employing a Classroom Action Research (CAR) approach. The participants were 67 second-semester students of the Tax Accounting Study Program at Balikpapan State Polytechnic. The intervention was conducted in two cycles, each consisting of planning, action, observation, and reflection. Findings revealed a consistent improvement in students’ performance. The pre-test recorded an average score of 51.76, indicating initial difficulties in vocabulary use, pronunciation, grammar, and fluency. In the first cycle, students showed better engagement and confidence, with the average score rising to 62.35 in Post-test 1. By the second cycle, further progress was evident as students became more fluent and collaborative, achieving an average score of 75.02 in Post-test 2. These results confirm that the TSTS strategy effectively enhanced not only test performance but also classroom interaction, self-confidence, and willingness to communicate. The study highlights the significance of cooperative learning models in fostering both linguistic competence and active participation in English language classrooms. The findings imply that integrating cooperative learning strategies such as TSTS can provide a practical and replicable approach for educators seeking to improve communication skills and learner engagement in English language settings.